Impact of creative capacity building of local innovators and communities on income, welfare and attitudes in Uganda: a cluster randomized control trial approach - Nkonya, Ephraim; Bashaasha, Bernard; Kato, Edward; Bagamba, Fredrick; Danet, Marion (International Initiative for Impact Evaluation, 2019)
Technologies and innovations are a key driver of human developments and competitiveness. Failure of imported technologies has galvanized efforts on technologies generated by close collaboration between external investors and local committees. The general objective of the study was to determine the impact of Creative Capacity Building (CCB) training on human welfare and local communities’ perception on their ability to innovate. Specifically, the study targeted a number of major outcomes of CCB training namely, economic impacts, behavioral changes, attitudinal change and technology creation and use including policy influence. CCB is a hands-on training approach whose students are community members with any educational level. CCB focuses on harnessing local creativity and indigenous knowledge in the technology design process, facilitating community innovations and invention. In skills training workshops, trainees work collaboratively to design and develop tools that meet their needs. The training encourages and trains people to make technologies that generate income, improve health and safety, save labour and time and change perceptions about themselves.
Keywords: Capacity building; Local innovators; Income; Welfare and attitudes